Acetabular Dysplasia: a Modern View of the Problem (Literature Review) - Filipchuk , V.V.; Suvorov , V.L. (TERRA ORTHOPAEDICA, 2020)
Summary. Hip dysplasia is the most common orthopedic problem in the practice of pediatric orthopedists. A significant problem with hip dysplasia is the divergence of nomenclature units, which is related to different points of view on the pathophysiology of the process. Contemporary conception defines hip dysplasia as a dynamic condition – “developmental dysplasia of the hip (DDH)”, which (in the absence of treatment) worsens with age and leads to the development of early hip osteoarthritis and requires hip replacement in young people. The leading macromorphological substrate of DDH is acetabular dysplasia, which is a spatial and structural change of acetabulum. For the treatment of acetabular dysplasia, conservative or surgical treatment (depending on the age of the child and the presence of previous treatment) is used. The most problematic solution is the treatment tactics for walking-age children. This is due to two factors: 1) increased loading on certain parts of the articular cartilage of the acetabulum during gait, which leads to the progression of deformity of the acetabulum and to progression of pathology; 2) changes in morphology of the intra-articular and extra-articular structures. However, better results with fewer complications are achieved after surgery. Biomechanically justified for acetabular dysplasia are pelvic osteotomies, which are divided into reconstructive and “salvage” procedures (preference is given to reconstructive procedures, which allows saving the native articular cartilage of acetabulum). Each osteotomy has its own advantages and disadvantages. When comparing three pelvic osteotomies commonly used in children (Salter, Pemberton and Dega), it is found that better results are achieved in children younger than 4 years after Salter’s osteotomy, results in older children are better after Dega’s osteotomy, and there is a high risk of femoroacetabular impingement following Pemberton’s osteotomy in the future.